Peningkatan Penggunaan Antibiotik Bijak pada Kelompok Pemberdayaan Wanita di Daerah Perkotaan di Kabupaten Banyumas Melalui Tindakan Intervensi KAP (Knowledge, Attitude, Practice) - Dwi Utami Anjarwati; Rahmawati Wulan Sari; Diyah Woro Dwi Lestari (Universitas Mathla'ul Anwar Banten, 2019)
INCREASING OF THE USE OF WISE ANTIBIOTIC IN WOMAN'S EMPOWERMENT GROUP IN THE URBAN AREA OF BANYUMAS REGENCY BY PROVIDING INTERVENTION OF KAP (KNOWLEDGE, ATTITUDE, PRACTICE). Unwise use of antibiotic behavior in the community contributes significantly to the increase in the incidence of antibiotic resistance. Antibiotic resistance has become a major health problem throughout the world that must receive attention both in hospitals and in the community. The purpose of this community service is as an effort to increase the use of wise antibiotics in women's empowerment groups in urban areas in Banyumas Regency by intervening Knowledge, Attitude, Practice (KAP). The target audience was an urban community group in Banyumas regency, namely all members of the Rambutan women's empowerment group located at Jl. Kalijaga, Berkoh, Purwokerto. The activities carried out for KAP intervention were knowledge transfer, and educational video included antibiotics, the wise use of antibiotics, and the dangers of antibiotic resistance. The results of the KAP intervention were measured by questionnaires containing statements from aspects of Knowledge, attitude, practice before and after KAP intervention activities. Each statement in the questionnaire was assessed with a Likert scale and tested for its validity and reliability. Data were analyzed descriptively while testing the results of questionnaires I and II were carried out by paired T-Tests. Data that can be analyzed are 39 respondents. The results of the questionnaire analysis showed an increase in KAP about antibiotic use before and after KAP interventions in women's empowerment groups in urban areas of Banyumas Regency. The article concluded that KAP intervention actions could achieve an increase in the use of wise antibiotics in women's empowerment groups in urban areas in Banyumas Regency.